Injectable catalyst-free "click" organic-inorganic nanohybrid (click-ON) cement for minimally invasive in vivo bone repair. (September 2021) - Liu, Xifeng; Camilleri, Emily T.; Li, Linli; Gaihre, Bipin; Rezaei, Asghar; Park, Sungjo; Miller II, A. Lee; Tilton, Maryam; Waletzki, Brian E.; Terzic, Andre; Elder, Benjamin D.; Yaszemski, Michael J.; et al.
Abstract: Injectable polymers have attracted intensive attention in tissue engineering and drug delivery applications. Current injectable polymer systems often require free-radical or heavy-metal initiators and catalysts for the crosslinking process, which may be extremely toxic to the human body. Here, we report a novel polyhedral oligomeric silsesquioxane (POSS) based strain-promoted alkyne-azide cycloaddition (SPAAC) "click" organic-inorganic nanohybrids (click-ON) system that can be click-crosslinked without any toxic initiators or catalysts. The click-ON scaffolds supported excellent adhesion, proliferation, and osteogenesis of stem cells. In vivo evaluation using a rat cranial defect model showed outstanding bone formation with minimum cytotoxicity. Essential osteogenic alkaline phosphatase (ALP) and vascular CD31 marker expression were detected on the defect site, indicating excellent support of in vivo osteogenesis and vascularization. Using salt leaching techniques, an injectable porous click-ON cement was developed to create porous structures and support better in vivo bone regeneration. Beyond defect filling, the click-ON cement also showed promising application for spinal fusion using rabbits as a model. Compared to the current clinically used poly (methyl methacrylate) (PMMA) cement, this click-ON cement showed great advantages of low heat generation, better biocompatibility and biodegradability, and thus has great potential for bone and related tissue engineering applications.